Boundary behavior of ring Q-homeomorphisms on Riemannian manifolds - Afanas'eva, E. S. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We study the problems of a continuous and homeomorphic extension of so-called ring $Q$-homeomorphismsbetween domains on Riemannian manifolds to the boundary. We establish conditions for a function $Q(x)$ andthe boundaries of domains under which every ring $Q$-homeomorphism admits a continuous or homeomorphicextension to the boundary. This theory can be applied, in particular, to Sobolev classes.